New records of the water mite family Arrenuridae from the Afrotropical region, with the description of 11 new species and two new subspecies (Acari: Hydrachnidia) - Smit, Harry (Zootaxa, 2012)
Ten new species and two new subspecies of the water mite genus Arrenurus are described from the Afrotropical region,i.e. Arrenurus abyssinicus n. sp., A. altomontanus n. sp., A. baleensis n. sp., A. bechuanicus n. sp., A. botswanicus n. sp.,A. coronopetiolatus n. sp., A. flavus n. sp., A. monocavus n. sp., A. okavango n. sp. and A. serratipetiolatus n. sp., A.chutteri longipes n. subsp., A. concavus longifissus n. subsp. One new species of the genus Thoracophoracarus is de-scribed, T. fluviatilis n. sp. The following taxa are proposed to the rank of a full species: A. chutteri K.O. Viets, A. damasiLundblad and A. grandis Walter & Bader. Arrenurus odonatophilus Müchberg is transferred to the subgenus Brevicau-daturus Smit, while A. discretus Cook is synonymized with the latter species. Arrenurus vanopus Cook is synonymizedwith A. capensis Thor, and the female of A. petri Cook must be assigned to A. capensis. The presumed female of A. petriis described therefore again. The male of A. latifoliatus K. Viets is redescribed and the female of this species is described for the first time.